Differential expression of osteopontin, and osteoprotegerin mRNA in epicardial adipose tissue between patients with severe coronary artery disease and aortic valvular stenosis: association with HDL subclasses - María Luna-Luna; David Cruz-Robles; Nydia Ávila-Vanzzini; Valentín Herrera-Alarcón; Jesús Martínez-Reding; Sergio Criales-Vera; Julio Sandoval-Zárate; Jesús Vargas-Barrón; Carlos Martínez-Sánchez; Armando Roberto Tovar-Palacio; José Manuel Fragoso; Elizabeth Carreón-Torres; et al. (Lipids in Health and Disease, 2017)
Abstract Background Previous studies suggest a relationship of the epicardial adipose tissue (EAT) with progression and calcification of the atherosclerotic plaque; however, it is unknown if this tissue expresses genes that may participate on these processes and if the expression of these genes is regulated by high-density lipoprotein (HDL) subclasses. Methods To explore this possibility, we determined the mRNA expression by qPCR of a pro-calcifying gene (osteopontin (OPN)), and two anti-calcifying genes (osteoprotegerin (OPG) and osteonectin (ON)), in biopsies of EAT obtained from 15 patients with coronary artery disease (CAD) determined by angiography, and 15 patients with diagnostic of aortic valve stenosis but without CAD as control group. We determined the distribution and composition of HDL subclasses by electrophoresis and their statistical relationship with the gene expression in EAT. Results EAT from CAD patients showed a higher expression level of OPN and OPG than control group, whereas ON expression was similar between groups. Large HDL subclasses were cholesterol-poor in CAD patients as estimated by the cholesterol-to-phospholipid ratio. A linear regression model showed an independent association of OPN expression with HDL3a-cholesterol, and OPG expression with the relative proportion of HDL3b protein. Logistic analysis determined that OPN expression was positively associated with the presence of atherosclerotic plaque Conclusion OPN, ON, and OPG genes are transcribed in EAT; to the exception of ON, the level of expression was different in CAD patients and control group, and correlated with some HDL subclasses, suggesting a new role of these lipoproteins.